Peran Lingkungan Sosial Pendidikan Terhadap Kesejahteraan Anak Usia Dini - Chylla Melinda Martien; Risbon Sianturi; Taopik Rahman; Mila Amelia Safitri; Nazwa Fazrina Kosasih; Syarla Salsabila Nurpadilah (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This research aims to find out the role of the social envirovment of education on the well-being of early childhood. The method used in this research is a library study method with a descriptive approach. Data obtained through various sources as books, journals, and scientific articles related to the research topic. Research results show that social envirovment of education has an important role in supporting the well-being of early childhood, especially is aspects of social, emotional, and cognitive develovment. An envirovment that tends to be conducive and positive can help children feel safe, comfortable, and develop optimally. From this topic, envirovment of education is an great influence on the well-being of early childhood